Palladium Nanoparticles Supported on a Metal–Organic Framework‐Partially Reduced Graphene Oxide Hybrid for the Catalytic Hydrodeoxygenation of Vanillin as a Model for Biofuel Upgrade Reactions. Issue 3 (6th January 2017) - Ibrahim, Amr Awad; Lin, Andrew; Zhang, Fumin; AbouZeid, Khaled M.; El‐Shall, M. Samy
Abstract: In this work we report a new strategy to enhance the catalytic activity and selectivity in heterogeneous catalysis by using a hybrid support that consists of metal–organic framework (MOF) crystals and partially reduced graphene oxide (PRGO) nanosheets to disperse metal nanoparticle catalysts efficiently. We report the development of a Pd nanocatalyst incorporated within a 3 D hierarchical nanocomposite that consists of a Ce‐based MOF wrapped with thin PRGO nanosheets, Pd/PRGO/Ce‐MOF, as a heterogeneous tandem catalyst for the hydrodeoxygenation of vanillin, a common component in lignin‐derived bio‐oil, under mild reaction conditions. Our results demonstrate that the PRGO/Ce‐MOF hybrid scaffold is an excellent support for Pd nanoparticles for the transformation of vanillin into 2‐methoxy‐4‐methyl phenol, an important high‐value phenol compound that can be used directly in the chemical and pharmaceutical industries. The high catalytic performance of the Pd/PRGO/Ce‐MOF catalyst is attributed to the unique characteristics of the incorporation of the PRGO support that leads not only to a stable and uniform dispersion of the Pd nanoparticles but also to the presence of acidic active sites that promote the hydrogenolysis reaction. Abstract : Wrap it up : We report the development of a Pd nanocatalyst incorporated within a 3 D hierarchical nanocomposite that consists of a Ce‐based metal–organic framework (MOF) wrapped in thin partially reduced graphene oxide (PRGO) nanosheets, Pd/PRGO/Ce‐MOF, as a heterogeneous tandem catalyst for the hydrodeoxygenation of vanillin under mild reaction conditions.